1971
DOI: 10.1530/jrf.0.0270227
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Boar Seminal Plasma, Vesicular Secretion and Epididymal Plasma Proteins by Gel Disc Electrophoresis and Isoelectric Focusing on Polyacrylamide

Abstract: Boar seminal plasma, vesicular secretion and epididymal plasma proteins were studied by gel disc electrophoresis at pH 4\m=.\5and 8\m=.\6and by isoelectric focusing in tubes and on plates using ampholines of pH range 3 to 10.The number of protein bands obtained in the gel disc electrophoresis was fifteen to twenty for all the samples. A similarity between the proteins of the seminal plasma and the vesicular secretion was greater at pH 4\m=.\5than at pH 8\m=.\6.The epididymal plasma showed a different separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
6
16
1
Order By: Relevance
“…This supports the notion that electrostatic interactions between proteins and other membrane components play important roles in a variety of cellular processes [52]. Although membranes used for our study were never exposed to seminal plasma, it is known that basic proteins are highly abundant in seminal plasma [53], and at least several of these interact directly with components of the sperm plasma membrane after ejaculation [54, 55]. These interactions have physiological importance in terms of acquisition and maintenance of motility [5658], or prevention of activation of signaling cascades involved in capacitation [55, 59].…”
Section: Discussionsupporting
confidence: 82%
“…This supports the notion that electrostatic interactions between proteins and other membrane components play important roles in a variety of cellular processes [52]. Although membranes used for our study were never exposed to seminal plasma, it is known that basic proteins are highly abundant in seminal plasma [53], and at least several of these interact directly with components of the sperm plasma membrane after ejaculation [54, 55]. These interactions have physiological importance in terms of acquisition and maintenance of motility [5658], or prevention of activation of signaling cascades involved in capacitation [55, 59].…”
Section: Discussionsupporting
confidence: 82%
“…1) was eighteen, and twelve or more of these could be detected in the sperm-rich fraction (Plate 1, Figs 3 and 4). This number was greater than the three proteins obtained by Einarsson et al (1970) using paper electrophoresis at pH 8-6, a pH shown by Lavon & Boursnell (1971) to be unsuitable for boar SP, VS and EP protein differentiation.…”
Section: Discussioncontrasting
confidence: 58%
“…Instruments, South Croydon) which were prepared and used as described by Lavon & Boursnell (1971) and by Lavon (1972). The correlation coefficients between the various parameters were calculated according to the method described by Bliss (1967).…”
Section: Isoelectric Focusingmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophoretic pattern of CEP has been reported for rams (Alumot et al, 1971) and boars (Einarsson, Crabo & Ekman, 1970;Lavon & Boursnell, 1971). The broad spectrum of proteins detected in bovine CEP was thus expected.…”
Section: Resultsmentioning
confidence: 79%